1996
DOI: 10.1046/j.1526-4610.1996.3602091.x
|View full text |Cite
|
Sign up to set email alerts
|

β‐Endorphin in Plasma and Monocytes in Juvenile Headache

Abstract: Interictal serum levels of serotonin and plasma and mononuclear cell concentrations of beta-endorphin were measured in 20 juvenile patients (13 suffering from migraine without aura and 7 from episodic tension-type headache) before and after 3 months of L-5-hydroxytryptophan treatment (5 mg/kg/day) and compared with a control group of 17 headache-free healthy subjects. While no significant differences in serum serotonin levels emerged between the three groups (migraine 104.6 +/- 26 micrograms/L, tension-type he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Conversely, our findings are consistent with those of a recent study performed by Battistella et al 46 who demonstrated a significant reduction in the levels of β-endorphins in PBMCs of both migraine and tension-type headache juvenile patients compared with age-matched control subjects, but did not show a significant difference in these levels between the two forms of headache.…”
Section: Commentssupporting
confidence: 93%
“…Conversely, our findings are consistent with those of a recent study performed by Battistella et al 46 who demonstrated a significant reduction in the levels of β-endorphins in PBMCs of both migraine and tension-type headache juvenile patients compared with age-matched control subjects, but did not show a significant difference in these levels between the two forms of headache.…”
Section: Commentssupporting
confidence: 93%
“…β-EP concentrations were decreased in CSF (SMD: –1.37, 95% CI: –1.80, –0.94) (30,3739) and blood (SMD: –0.76, 95% CI: –1.17, –0.36) (38,63,64) from chronic migraine patients. Concentrations were also decreased in CSF (SMD: –1.12, 95% CI: –1.65, –0.58) (37,38,40) and blood (SMD: –0.40, 95% CI: –0.64, –0.16) (38,40,6573) from interictal patients. Pooled estimates remained similar in sensitivity analysis.…”
Section: Resultsmentioning
confidence: 97%
“…For comparison group f, ictal vs interictal also refers to the active cluster bout vs remission. In addition to the references from Table 3 with clear blood specimen descriptions (n = 30), 15 references were included 21,26,27,37,39,43,48,125‐132 . Abbreviations: chronic cluster headache (CCH); chronic migraine (CM); control (CTRL); episodic cluster headache (ECH); female/female‐dominated (F/FD); migraine (M); both sexes (M/F); male/male‐dominated (M/MD); migraine with aura (MWA); migraine without aura (MWoA).…”
Section: Resultsmentioning
confidence: 99%